Author Correction: Dopamine-dependent prefrontal reactivations explain long-term benefit of fear extinction - A. M. V. Gerlicher (Nature Portfolio, 2019)
In the original version of this Article, the fourth sentence of the legend to Figure 1b incorrectly read “Note, that the group difference stemmed from significantly smaller CS+ evoked SCRs averaged across the whole test phase, but the speed of re-extinction did not differ significantly between drug groups (control analysis with stimulus (CS+, CS−) and trial (1–10) as within-, and group (placebo, L-DOPA) as between-subject factor: stimulus × group, F 1,297 = 6.57, P = 0.02, partial η 2 = 0.17; stimulus × trial × group, F 1,297 = 1.32, P  = 0.23; n = 35)”. The correct version states “F 1,33 = 6.58” instead of “F 1,297 = 6.57”, and “F 9,297 = 1.32” instead of “F 1,297 = 1.32”. These errors have now been corrected in both the PDF and HTML versions of the Article. The correct values were used in the statistical analysis and the errors do not affect the conclusions.